Evaluasi Program PIPOCITA di UPT SD Negeri Tamalanrea Makassar dengan Model Evaluasi CIPP - Rahmawati, Rahmawati; Rasyid, Muhammad Nur Akbar; Syamsudduha, Siti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study evaluates one of the educational programs at UPT SD Negeri Tamalanrea, namely the PIPOCITA (Our Little Police Picket) program. This program was evaluated using CIPP Evaluation Model which analysed Context, Input, Process and Product of the program. Data were collected using interviews, observation and documentation. The study involved teachers, students and parents. The results showed that the evaluation of the context of this program met the evaluation criteria for the context of a program, namely the existence of goals to be achieved. The input evaluation contained various resources in carrying out the program, namely the presence of picket schedules, resources for carrying out pickets, and the presence of students and teachers who will do pickets. In the evaluation process, it was found that this program was carried out in groups based on the picket schedule and the person in charge to do the picket are still carrying out supervision and evaluation in each program implementation. The evaluation of the Product found that the results of this program made students more independent and had emotional relationships with teachers, students and parents. Therefore, the PIPOCITA program still needs to be adjusted and improved from various aspects according to the characteristics of students and parents and the community in the school area.